KOMUNIKASI PEMASARAN DIGITAL PRODUK CAKE AND COOKIES DALAM MENINGKATKAN PENJUALAN KOMUNITAS UMKM - Aprilyanti Pratiwi; Nazhifa Kamila; Winda Haifa (Universitas Prof. Dr. Moestopo (Beragama), 2023)
There has been a change in marketing strategy, from traditional to modern. Modern marketing strategy was chosen because it has several advantages, such as wide market and cheap promotional costs. One of users modern marketing strategies is MSMEs. Modern or digital marketing has proven to be influential in showing the advantages of MSME products so they can compete with competitors. Purpose of the study is to analyze digital marketing communication activities carried out by Teras Ciapus MSME community in promoting cake and cookies products. This is qualitative research with interview and digital observations. The digital marketing communication activities carried out by Teras Ciapus MSME community were not optimal. The account used to promote the products is their personal account. They have not taken full advantage of the features available on social media it’s because they do not really understand the functions and uses of the features on it. It takes the role of a number of external parties, such as the banking, the Ministry of MSMEs, academics and practitioners who have concentration on MSME digital literacy.